Pelatihan Tahsin Tilawah dan Tahfizh AlQur’an Dalam Pembinaan Karakter dan Spritualitas Pelajar di PNNS Malaysia - Wathan, Hubbul; Suherman; Kamil, Idham; Lubis, Muhammad Arif Fadillah; Mabrur, Muhammad (Politeknik Negeri Medan, 2024)
Tilawah and Tahfizh Al-Qur'an Program. This educational program aims to improve the ability to read the Qur'an with tartil and according to the rules of tajweed, strengthen the memorization of the Qur'an, and instill a love for the Qur'an and practice its contents. This program aims to improve proficiency and fluency in reading the Qur'an through Mohsin (lettering and tajweed) and catfish (memorization) approaches. The collaboration between Politeknik Negeri Medan (Polmed) and Politeknik Nilai Negeri Sembilan (PNNS) integrates a comprehensive curriculum, interactive teaching, and close supervision to ensure each participant can achieve the desired level of proficiency. The program not only focuses on academic aspects but also on spiritual development and Islamic values.